2019
DOI: 10.3847/2041-8213/aafb07
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Another Intermediate-mass Black Hole in the Galactic Center

Abstract: We report the discovery of molecular gas streams orbiting around an invisible massive object in the central region of our Galaxy, based on the high-resolution molecular line observations with the Atacama Large Millimeter/submillimeter Array (ALMA). The morphology and kinematics of these streams can be reproduced well through two Keplerian orbits around a single point mass of (3.2±0.6)×10 4 M . We also found ionized gas toward the inner part of the orbiting gas, indicating dissociative shock and/or photoionizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
1
35
2
Order By: Relevance
“…We conclude with the remark that Kepler's game changing three laws remain as relevant to our exploration of the universe and the laws that govern it today as when they were first formulated. No better illustration of this fact may be found than in [26,27]. Studying the motion of matter around a black hole could provide a test for the validity/corrections of Kepler's laws at the large scale.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude with the remark that Kepler's game changing three laws remain as relevant to our exploration of the universe and the laws that govern it today as when they were first formulated. No better illustration of this fact may be found than in [26,27]. Studying the motion of matter around a black hole could provide a test for the validity/corrections of Kepler's laws at the large scale.…”
Section: Discussionmentioning
confidence: 99%
“…We also discuss the effect from a possible massive dark perturber, such as an intermediate-mass black hole. A number of IMBH candidates have been suggested near the Galactic Center [54][55][56]. An IMBH orbiting around the black hole can cause Kozai oscillations of the orbital parameters of a star if the IMBH is located outside of the stellar orbit.…”
Section: Effects From Ambient Perturbersmentioning
confidence: 99%
“…Medium-weight seeds would extend the correlation between the stellar and nuclear black hole masses to dwarf galaxies (Greene et al 2010;Safonova & Shastri 2010;Reines & Volonteri 2015;Mezcua et al 2018), they could explain the existence of Ultra Luminous X-ray sources (Miller et al 2004;Fritze et al 2018;Shen 2019;Barrows et al 2019;Baldassare et al 2020), and are necessary to prevent tidal distruption events in young star clusters observed in the galactic nucleus (Kim et al 2004). These ∼ 10 3 M BHs will be targeted by future third-generation gravitational telescopes, such as the Laser Interferometer Space Antenna (LISA) (Coleman Miller & Hamilton 2002;Sesana et al 2005; Amaro-Seoane & Santamaria 2010; Kremer et al 2019), but recent observations (Ballone et al 2018;Argo et al 2018;Takekawa et al 2019;Nguyen et al 2019;Woo et al 2019;Barack et al 2019) have found evidence of their existence in the Local Universe.…”
Section: Introductionmentioning
confidence: 99%